Control of ultrafast pulses in a hydrogen-filled hollow-core photonic-crystal fiber by Raman coherence - Belli, F. (2018)
We present the results of an experimental and numerical investigation into temporally nonlocal coherent interactions between ultrashort pulses, mediated by Raman coherence, in a gas-filled kagome-style hollow-core photonic-crystal fiber. A pump pulse first sets up the Raman coherence, creating a refractive index spatiotemporal grating in the gas that travels at the group velocity of the pump pulse. Varying the arrival time of a second, probe, pulse allows a high degree of control over its evolution as it propagates along the fiber through the grating. Of particular interest are soliton-driven effects such as self-compression and dispersive wave (DW) emission. In the experiments reported, a DW is emitted at ∼300nm and exhibits a wiggling effect, with its central frequency oscillating periodically with pump-probe delay. The results demonstrate that a strong Raman coherence, created in a broadband guiding gas-filled kagome photonic-crystal fiber, can be used to control the nonlinear dynamics of ultrashort probe pulses, even in difficult-to-access spectral regions such as the deep and vacuum ultraviolet.